2021
DOI: 10.3390/rs13112156
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rain-Induced Attenuation over Signal Links at Frequency Ranges of 25 and 38 GHz Observed in Beijing

Abstract: Wireless communication has become a very important part of our lives, and it is well known that meteorological factors affect the quality of communication links, especially at higher frequencies because the physical dimensions of raindrops, hail stones, and snowflakes are on a similar wavelength to the propagating radio frequency. Millimeter-waves are an important technology for fifth-generation cellular networks which are currently being deployed all over the world. Since atmospheric effects are challenging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Song et al [32] calculated the specific attenuation and rainfall intensity based on DSD, and then the relationship between specific attenuation and rainfall intensity was obtained by using nonlinear fitting. Han et al [33] also confirmed that the coefficients a and b in k-R relationship of stratiform and convective rain can be estimated based on local DSD measurement, and compared to the coefficients in the ITU-R P.838 document, the derived coefficients achieved an improved rain rate estimation. DL has outstanding advantages in solving the problem of complex dependent data association mining.…”
Section: Path-average Rain Rate Estimationmentioning
confidence: 83%
See 1 more Smart Citation
“…Song et al [32] calculated the specific attenuation and rainfall intensity based on DSD, and then the relationship between specific attenuation and rainfall intensity was obtained by using nonlinear fitting. Han et al [33] also confirmed that the coefficients a and b in k-R relationship of stratiform and convective rain can be estimated based on local DSD measurement, and compared to the coefficients in the ITU-R P.838 document, the derived coefficients achieved an improved rain rate estimation. DL has outstanding advantages in solving the problem of complex dependent data association mining.…”
Section: Path-average Rain Rate Estimationmentioning
confidence: 83%
“…The attenuation caused by rainfall and the average rain rate are linearly correlated if b ≈ 1. Other than Equation ( 1), the values of the rain rate R and the specific attenuation k can be estimated based on DSD refer to [32,33], i.e.,…”
Section: Path-integrated Rain Attenuationmentioning
confidence: 99%
“…The rain measurement was conducted on the roof of building 40 of IAP, ∼950 m to the northeast of the sampling site, using an OTT Parsivel 2 precipitation particle disdrometer (https://www.ott.com/products/meteorological-sensors-26/ott-parsivel2-laser-weather-sensor-2392) with time resolution of 10 s from 2019 to 2022 (Han et al., 2021). The rainfall intensity (RI) was then calculated and compared with that obtained at eight meteorological stations in urban Beijing (Figure S1 in Supporting Information ), and the rainfall measurements at different sites agreed reasonably well (Luo et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…At presentIn the existing rainfall attenuation estimation methods, the basic idea is to estimate the statistical value of the maximum rainfall attenuation according to different time probabilities [4]. The difference only lies in the different values of rainfall area, rainfall intensity and rainfall height.…”
Section: Rainfall Attenuation Factormentioning
confidence: 99%